Minimally invasive burr hole craniotomy versus drill hole craniotomy for the management of chronic subdural hematoma: a randomized clinical trial - Eisenkolb, Viktor M.; Hoenikl, Lisa S.; Schwendinger, Nina; Obermueller, Thomas; Buchmann, Niels; Wagner, Arthur; Aftahy, Amir Kaywan; Krieg, Sandro; Meyer, Bernhard (Neurosurgical focus, 2025)
OBJECTIVE Chronic subdural hematoma (cSDH) is a frequently treated entity for neurosurgeons worldwide. Because this pathology is common in older patients and those with multiple comorbidities, the demographic shift increases pressure on healthcare systems, which already face major economic challenges. Various surgical procedures are used, although the high recurrence rate leads to the even greater importance of standardizing the medical approach. Therefore, the aim of this study was to compare bedside cSDH evacuation using hollow screws (HSs) under local anesthesia with evacuation using enlarged burr holes (BHs) under general anesthesia. METHODS This prospective randomized study, conducted at a single center from September 2015 to August 2020, included patients with space-occupying (hematoma thicker than the skull) and/or symptomatic cSDH who underwent surgical treatment. During the study period, 140 patients were enrolled and 9 patients were excluded. RESULTS A total of 131 patients (mean age 77 years) were included in the analysis. HS trephination demonstrated comparable recurrence rates to that of BH trephination (BH 31.2% vs HS 47.8%, p = 0.06) and equivalent clinical outcomes (p > 0.05). Yet, HS placement was a less invasive surgical approach associated with a significantly shorter operation duration (p < 0.05) and shorter hospital stay (median BH 4.3 days vs HS 3.0 days, p = 0.003). CONCLUSIONS In treating cSDH, HS trephination should be considered a reasonable alternative to BH trepanation, especially with the demographic changes occurring in modern society and the associated requirements for healthcare systems.